Gambaran Karakteristik Pasien Fraktur Klavikula di Rumah Sakit Umum Pusat (RSUP) Sanglah Periode Januari-Desember 2019 - Devinta, Made Ratih Santi; Asmara, Anak Agung Gde Yuda; Dharmayuda, Cokorda Gde Oka (Universitas Udayana, 2022)
Clavicle fracture is a common cause of injuries in adult, with over 2.6?4% of cases have been found with an incidence rate of 30 over 100.000 population. Although having a high incidence rate, availability of studies on the characteristics of clavicle fractures in Indonesia remains limited. Based on the high incidence of cases, variability of concomitant injuries and the evolution of science and technologies in health, this study was conducted to discover the characteristics of clavicle fractures patients in Rumah Sakit Umum Pusat (RSUP) Sanglah Denpasar. This study used a cross sectional approach with descriptive retrospective as the study design and using secondary data of clavicle fracture patients in RSUP Sanglah in January?December 2019. Secondary data used in this study were obtained from the Morning Reports of Orthopaedic and Traumatology Department in RSUP Sanglah. Variables in this study including age, gender, type of fracture, type of concomitant injuries and type of treatment. The data was obtained using total sampling technique. Among 91 cases of clavicle fracture, they were mainly found in a group of young productive men (17?25 years old) and mostly classifed as closed fractures (97.8%). Most of the patients came with head injuries (45.1%) and thorax injuries (45.1%) and mainly went through surgical procedures (ORIF) 74.7%.